Winnie's new computer - Thomas, Valerie; Paul, Korky (Oxford University Press Oxford, 2015)
Winnie, the Witch is very pleased with her new computer. She decides that from now on all her magic will be at the click of a mouse. When Wilbur tries to pounce on the mouse, things start to go wrong. Winnie wakes up to discover she has no cat, and no computer. She could really use a little magic, but just where is it going to come from?